Magnesium-based alloys for solid-state hydrogen storage applications: A review. (1st September 2021) - Hitam, C.N.C.; Aziz, M.A.A.; Ruhaimi, A.H.; Taib, M.R.
Abstract: Magnesium hydrides (MgH2 ) have attracted extensive attention as solid-state H2 storage, owing to their low cost, abundance, excellent reversibility, and high H2 storage capacity. This review comprehensively explores the synthesis and performance of Mg-based alloys. Several factors affecting their hydrogen storage performance were also reviewed. The metals addition led to destabilization of Mg–H bonds to boost the dehydrogenation process. A unique morphology could provide more available active sites for the dissociation/recombination of H2 and allow the activation energy reduction. Also, an appropriate support prevent the agglomeration of Mg particles, hence, sustains their nanosize particles. Moreover, the perspective of avenues for future research presented in this review is expected to act as a guide for the development of novel Mg-based H2 storage systems. New morphological shape of catalysts, more unexplored and highly potential waste materials, and numerous synthesis procedures should be explored to further enhance the H2 storage of Mg-based alloys. Highlights: Alloying of Mg is an efficient strategy to enhance hydrogen storage performance. Numerous synthesis route could be explored to produce effective Mg-based alloy. Diverse metal loadings could differently affect the hydrogen storage performance. Proper morphology can hasten dissociation and recombination of hydrogen. Appropriate supports sustain the nanosize and disperse the vital species in alloys.